1993
DOI: 10.3168/jds.s0022-0302(93)77602-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inert Fat on Energy Balance, Plasma Concentrations of Hormones, and Reproduction in Dairy Cows

Abstract: The objective was to determine the effects of dietary inert fat on estimated energy balance, hormones in plasma, and reproduction during early lactation. From wk 0 to 12 postpartum, 14 pluriparous Holstein cows were fed individually a TMR, and blood samples were taken twice weekly for quantification of IGF-I, progesterone, and cholesterol. During wk 5 to 12, one-half of the cows remained on the TMR, and the other half were fed the TMR containing inert fat at 1.8% of dietary DM. Estrous behavior was monitored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
2
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 25 publications
8
31
2
1
Order By: Relevance
“…The negative energy balance is directly related to the postpartum interval to first ovulation, and follicle size was adversely affected by negative energy balance in early postpartum dairy cows [9]. The average EB during the first 4 week of lactation was negatively correlated to the postpartum interval to first ovulation [57]. …”
Section: Effect Of Evaporative Cooling System On Energy Balance and Bmentioning
confidence: 92%
“…The negative energy balance is directly related to the postpartum interval to first ovulation, and follicle size was adversely affected by negative energy balance in early postpartum dairy cows [9]. The average EB during the first 4 week of lactation was negatively correlated to the postpartum interval to first ovulation [57]. …”
Section: Effect Of Evaporative Cooling System On Energy Balance and Bmentioning
confidence: 92%
“…In general, the negative effect of extra lipogenic sources on dry matter intake is higher when the degree of saturation of fatty acids is lower, probably because of the more pronounced negative effects of unsaturated fatty acids on rumen carbohydrate fermentation. As a result, 73% of the studies on feeding extra lipogenic nutrients [15,61,63,65,75,100,101,104,106] and also 73% of the studies on increasing dietary glycogenic nutrients [61,[69][70][71][72]117] obtained a higher net energy (NE) intake in the treatment group compared to the control group, illustrated by Figure 4 shows an overview of studies that reported milk yield and composition after feeding either more glycogenic nutrients or lipogenic nutrients. Both feeding extra lipogenic nutrients or glycogenic nutrients had similar effects on kg of milk produced per day [8, 15, 60-72, 75, 77, 78, 82, 99-104, 106, 107, 110, 111, 115-122] …”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Energy Intakementioning
confidence: 99%
“…Figure 5 further supports these hypotheses, by presenting 18 studies on either feeding more lipogenic or glycogenic nutrients on the calculated EB. Eight of the 12 studies reported an increase in EB after feeding extra lipogenic nutrients [8, 9, 12, 15, 64,66,106]. In contrast to feeding extra glycogenic nutrients where 12 out of 13 studies were able to improve, not-significantly, the calculated EB [66,69,71,72,77,107,108,110,112,116,120].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Ebmentioning
confidence: 99%
“…Although cholesterol is a precursor of steroids, the concentration of total cholesterol, without contrast between free cholesterol and cholesterol ester, has been investigated for the relationship with the interval to 1st-OV in early postpartum dairy cows [15,16]. In our results, there was a significant correlation between the interval to the 1st-OV and the mean free cholesterol in the pre-OV period, indicating that the free cholesterol concentration in this period might be the factor restricting steroidgenesis in both the adrenal cortex [11] and ovaries [17,18].…”
Section: Discussionmentioning
confidence: 99%